Décès brutal et infection à virus Influenza A chez un enfant de deux ans : étude d’un cas autopsique - Marcorelles, P (Arch Pediatr, 2002)
Influenza A virus infections are common in childhood and infancy and are often underdiagnosed while serious or letal forms are rare. Case-report. – We describe a case of sudden death in a two-year-old boy. Pathologic findings at autopsy were consistent with Myxovirus influenzae A virus infection and the virus was isolated by post mortem PCR. Conclusion. – In the case of sudden death in infants, especially if pathologic findings are compatible with a viral infection, PCR may allow identification of the causative virus.